Relations between close friendships and adolescent aggression: Structural and behavioral friendship features2. Issue 2 (21st December 2017) - Andrews, Naomi C. Z.; Hanish, Laura D.; DeLay, Dawn; Martin, Carol Lynn; Updegraff, Kimberly A.
Abstract: Friendships have the potential to perpetuate or mitigate youth's aggressive behavior. We investigated concurrent and longitudinal effects of friendships on aggression by examining both structural (size and interconnectedness of the local friendship network) and behavioral (friends' aggression) friendship features. Participants were 868 sixth to eighth grade middle‐school students ( M  = 12.10 years; 49.9% girls; 44% Latina/o) who completed questionnaires at two time points. Participants nominated their friends; reciprocal friendship nominations were used to calculate structural friendship group features (size and interconnectedness). Peer nominations were also used to measure youth's and their friends' aggression. Having more reciprocal friends was associated with more aggression concurrently (particularly for youth whose friends were highly aggressive), and having an interconnected friendship group was associated with decreased aggression over time. Given that findings were different for group size and interconnectedness, we discuss the unique importance of each of these structural friendship features. Practical implications regarding the potential to decrease aggressive behavior based on specific friendship features are also discussed.